The Creation of Serbian Codes (1827–1865): Memories of the Contemporaries - Drakić, Gordana; Stanković, Uroš (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The article puts forth the information on drafting Serbian codes introduced up to 1865 inclusive existing in memoir literature. The contemporaries’ memories on code-creating are given in two chapters – records on codification of private law and notes on codification of public law. Each of these divisions contain memoir-writers’s notes in relation with the codes belonging to respective fields of law. The authors examined credibilty of the records and used them as the basis for further research on certain scarcely known details from Serbian code-drafting history. The research resulted in deepening already existing knowledge on the subject, but also in some new revelations.